Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/lary.28710
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Laryngeal Adductor Reflex Versus Intermittent Nerve Monitoring in Neck Endocrine Surgery

Abstract: Objective Intraoperative neuromonitoring (IONM) techniques aim to identify and potentially prevent nerve injury during surgeries. Prior studies into the efficacy of recurrent laryngeal nerve (RLN) IONM convey mixed results, with some claiming equivalence between IONM and no monitoring at all. The goal of the current study was to compare continuous RLN monitoring using the laryngeal adductor reflex (LAR) to intermittent RLN monitoring (intermittent IONM) to determine whether continuous monitoring reduces the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
(152 reference statements)
0
26
0
Order By: Relevance
“…Chiang et al suggest that the lack of a standardized IONM procedure could increase the risk of stretch injury to the RLN via Berry's ligament due to excessive traction and propose a standardized IONM procedure as a four‐step protocol 1,3 . The usefulness of intermittent nerve monitoring has been well documented 13‐16 . CIONM overcomes the key methodological limitation inherent to intermittent nerve monitoring, which allows the nerve to be at risk in between stimulations 8,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Chiang et al suggest that the lack of a standardized IONM procedure could increase the risk of stretch injury to the RLN via Berry's ligament due to excessive traction and propose a standardized IONM procedure as a four‐step protocol 1,3 . The usefulness of intermittent nerve monitoring has been well documented 13‐16 . CIONM overcomes the key methodological limitation inherent to intermittent nerve monitoring, which allows the nerve to be at risk in between stimulations 8,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, endotracheal tubes do not yet allow for simultaneous recording of bilateral LAR responses. VN, vagal nerve; RLN, recurrent laryngeal nerve techniques were reported to reduce the transient [36] and permanent [9••] VCP rate more effectively than intermittent IONM. These international results contradict contemporary meta-analyses, which concluded that the use of intraoperative nerve monitoring did not contribute to reduced VCP rates [19][20][21].…”
Section: Effect Of Ionm Usage On Postoperative Vcp Ratementioning
confidence: 99%
“…The other etiological factors of RLN injury such as cauterization, clamping, ligature, transection occur with sudden actions and these actions may not be prevented by C-IONM. [ 68 , 69 ]…”
Section: C-ionmmentioning
confidence: 99%